State of the Climate in Africa 2023 - World Meteorological Organization (World Meteorological Organization, 2024)
In Africa, 2023 was one of the three warmest years in the 124-year record, depending on the dataset used. The mean temperature was 0.61 °C higher than the 1991–2020 average and 1.28 °C higher than the 1961–1990 average. The African continent warmed at a rate of +0.3 °C/decade between 1991 and 2023, a slightly faster rate than the global average. 2023 was the warmest year on record in many countries, including Mali, Morocco, the United Republic of Tanzania, and Uganda. Morocco experienced the highest temperature anomaly, 1.25 °C above the 1991–2020 reference period. Extreme heatwaves in July and August affected northern Africa, with Tunis, Tunisia reaching a new maximum temperature of 49.0 °C, and Agadir, Morocco reaching a new maximum temperature of 50.4 °C. The rate of sea-level rise around Africa was close to or slightly higher than the global mean rate of 3.4 mm/year. The highest rate of sea-level rise, 4.1 mm/year, was observed in the Red Sea. Precipitation was notably higher than normal in Angola and coastal areas north of the Gulf of Guinea. Regions with a marked rainfall deficit included the western part of North Africa, the Horn of Africa, portions of Southern Africa, and Madagascar. Parts of Morocco, Algeria, Tunisia, Nigeria, Cameroon, Ethiopia, Madagascar, Zambia, Angola, and the Democratic Republic of the Congo experienced severe drought in 2023. At least 4 700 confirmed deaths in Libya have been attributed to the flooding that followed the Mediterranean cyclone Storm Daniel in September, with 8 000 people still missing. Parts of Kenya, Somalia and Ethiopia experienced widespread and severe flooding, with more than 350 deaths and 2.4 million people displaced during the April–June period. Climate extremes are becoming more frequent and severe and are disproportionately affecting African economies and societies. On average, climate-related hazards cause African countries to lose 2%–5% of their gross domestic product (GDP) annually, with many diverting up to 9% of their budgets to respond to climate extremes. In Tunisia, widespread drought conditions in 2023 resulted in cereal production being 80% below average. Rainfall deficits in Nigeria, Benin, and Ghana also led to localized shortfalls in agricultural production. In sub-Saharan Africa, it is estimated that climate adaptation will cost US$ 30 billion to US$ 50 billion per year over the next decade, 2%–3% of the regional GDP. Investing in National Meteorological and Hydrological Services and early warnings and early actions is a priority for saving lives, promoting economic development, valuing development gains and livelihoods and reducing the cost of disaster responses.